2021
DOI: 10.1002/jdn.10120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of omega 3 polyunsaturated fatty acids, antioxidants, and/or non‐steroidal inflammatory drugs in the brain of neonatal rats exposed to intermittent hypoxia

Abstract: Preterm infants experience frequent arterial oxygen desaturations during oxygen therapy, or intermittent hypoxia (IH). Neonatal IH increases oxidative distress which contributes to neuroinflammation and brain injury. We tested the hypotheses that exposure to neonatal IH is detrimental to the immature brain and that early supplementation with antioxidants and/or omega 3 polyunsaturated fatty acids (n‐3 PUFAs) combined with non‐steroidal anti‐inflammatory drugs (NSAIDs) is protective. Newborn rats were exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Omegaven, an Omega-3 triglyceride emulsion, has been shown to be neuroprotective in different preclinical animal models of newborn brain injury 55 . Docosahexaenoic acid (DHA) is one of the major omega-3 polyunsaturated fatty acids and it has been shown to be essential for development and function of the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Omegaven, an Omega-3 triglyceride emulsion, has been shown to be neuroprotective in different preclinical animal models of newborn brain injury 55 . Docosahexaenoic acid (DHA) is one of the major omega-3 polyunsaturated fatty acids and it has been shown to be essential for development and function of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Docosahexaenoic acid (DHA) is one of the major omega-3 polyunsaturated fatty acids and it has been shown to be essential for development and function of the brain. It reduces excitotoxicity, inflammation and free radical production following neonatal hypoxic-ischemic brain injury in different animal models 55 . We found that a single dose of Omegaven (0.75 mg/kg) (Table 1 ) administered immediately after hypoxia–ischemia was superior to a repetitive dosing regimen and significantly reduced brain area loss in our standardized model.…”
Section: Discussionmentioning
confidence: 99%
“…We utilized a model of neonatal IH developed in our laboratory that consistently produces oxidative stress, as previously reported (Manlapaz‐Mann et al, 2021; Soontarapornchai et al, 2021). In the rat, postnatal day 1–5 is the preterm equivalent of 23–32 weeks human gestation.…”
Section: Discussionmentioning
confidence: 99%
“…The IH profile consisted of an initial exposure of hyperoxia (50% O 2 ) for 30 minutes followed by three brief, 1‐minute, clustered hypoxic events (12% O 2 ), with a 10‐minute re‐oxygenation in 50% O 2 between each hypoxic event. Recovery from IH occurred in 50% O 2 following each clustered IH event for 2.5 hours for a total of eight clustering IH episodes per day for 14 days, as previously described (Manlapaz‐Mann et al, 2021; Soontarapornchai et al, 2021). Oxygen saturation was confirmed on a sentinel un‐anesthetized rat pup from each group using the MouseOx Pulse Oximeter and WinDaq Waveform Browser software (STARR Life Sciences Corp., Oakmont PA) before and after IH exposure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation